Conspiracy Theory Advocacy and Endorsement of Inaccurate Material: A Review of the Psychological Research 2010 - 2022 - Drinkwater, Kenneth; Dagnall, Neil; Denovan, Andrew (Journal of Scientific Exploration, 2023)
Since 2010 the number of psychological investigations examining relationships between conspiracy theory (CT) advocacy and endorsement of inaccurate material (i.e., misinformation, disinformation, and fake/false news) has increased exponentially. However, due to the breadth of topics investigated, the diversity of approaches/methods employed, and the range of data examined, the extent to which research in this domain provides a coherent body of work is unclear. Accordingly, this paper performed a review of psychological articles published in Web of Science and Scopus during the period January 2010 to May 2022. Search terms used were “conspir* AND misinformation OR disinformation OR "fake news" OR "false news". The articles selected had either collected primary data or analysed extant secondary data and were written in English. Forty-six articles were included in the review and the majority 87% (n = 40) were published between January 2018 and May 2022. This reflected the increase in interest in the topic and the concomitant development of the COVID-19 pandemic. Across the literature, there was a lack of conceptual clarity and congruence. This arose principally from the failure to adequately operationalize key terminology (i.e., definitions of conspiracy and inaccurate information) and/or use terminology consistently. This indicated that research in the field would benefit from the development of standardized operational conceptualizations and taxonomies. Given the breadth of the research across different academic disciplines and in related areas such as pseudoscience, this article should be regarded as extensive, rather than exhaustive. In this context, this review provides only insights into the nature of psychological research within the designated parameters. Future work is required to determine if investigations in allied areas demonstrate similar reporting trends to those observed in this article.